Hitting Two Birds with One Stone: A Phenomenological Inquiry of Junior High Math Buddies in a University - Soroño-Gagani, Flordeliza; Olvido, Michelle Mae; Bonotan, Amelia M. (European Scientific Journal, ESJ, 2019)
To provide adequate academic support services in the area of Mathematics, a peer tutoring program called Math Buddy was initiated and studied using phenomenology to capture the life experiences of the tutors and tutees who were purposively selected Grade 9 students in Mathematics. The descriptive analysis of the students’ weekly journals, written evaluations, observations, and focused group discussions had revealed the following themes: (1) challenging initial implementation; (2) embracing social responsibility; (3) understanding varying personalities; (4) recognizing benefits and incentives; (5) developing creativity and initiative. The students recognized that there were benefits and incentives derived from their participation in the program. They also admitted that it was a challenging task that developed their creativity and initiative because they have to understand varying personalities as they embrace their social responsibility. As the benefits outweigh the challenges, the researchers recommend that the program be continued.